Health Care Workers' Attitudes towards Antenatal Care Services in Babylon City - Jasim, Mahir Mohammed; Raheem, Saad Saleem (Journal of Neonatal Surgery, 2025)
Introduction: Antenatal care'' (ANC) is a mix of pregnant women's support, health education, preventative care and treatments, and monitoring for any issues affecting the mother and fetus. In primary care facilities, prenatal services are offered. In addition to hospitals, uncomplicated obstetric services may be provided in inadequately furnished and designated facilities. Objective: To Evaluate of, antenatal care services, in Babylon Governorate from the perspective of, health care workers. Methodology: This was a cross-sectional analytic study conducted at 22 randomly selected (simple random sampling) primary health care centers in al-Hilla city. The data collection started from the 27 0f October 2024 till the 27 of January 2025. The time allocated for data collection was an average 5 days per week. This study was conducted in AL-Hilla city. which included22 primary health care centers in the first Hilla sector and the second Hilla sector. Results: The results of the study showed that, the quality evaluation of (ANC) is usually seen positively by healthcare workers (HCWs) in primary healthcare centers (PHCs), as evidenced by the statistically significant services means in both the administration and performance dimensions. The mean scores for quality of performance (M = 3.34, SD = 0.540, p ≤0.05) and quality of administration (M = 3.65, SD = 0.668, p ≤0.05) show an overall good evaluation of ANC services, according to the one-sample t-test findings. Recommendations: The Ministry of Health should focus more on the services offered to expectant mothers, according to the report. The study also highlights the importance of increasing knowledge in order to improve women's health status by encouraging frequent visits to care facilities during the three phases of pregnancy.